Pendampingan Tata Kelola Badan Usaha Milik Desa (Bumdes) Bersama Di Desa Anjir Pasar Kabupaten Barito Kuala - Firdaus, M. Ananta; Ristiawati, Risni (Banua Law Review, 2023)
Village-owned businesses offer numerous advantages to village communities in terms of improving the village economy. BUMDes has set the goal of improving the village economy as one of its objectives. One of the objectives of establishing BUMDes is to eradicate poverty in the village community and to empower the village's potential. This community service will help the management of BUMDes Bersama in Anjir Pasar, Barito Kuala Regency and their business units. The outcomes of outreach activities for mentoring BUMDes governance can be used to plan work programs based on discussions between the PDWA team, village officials, BUMDes managers, and the local community. The mentoring for BUMDes governance provides solutions to problems encountered by other things related to all human resources for BUMDes managers, namely providing technical guidance, management of existing but not yet optimal BUMDes businesses (Local rice and handicraft, Fertilizer, Agricultural Equipment, Agricultural Medicine, and Harvest Services).